FORENSIC ANALYSIS OF COCAINE SAMPLES PRODUCED IN COLOMBIA: I. CHROMATOGRAPHIC PROFILING - GARZÓN M., William F.; PARADA A., Fabián; FLORIÁN R., Néstor M. (Vitae, 2009)
In this study sixty-five (65) seized samples of cocaine hydrochloride are chromatographically outlined to determine its purity and making qualitative analysis to detect adulterants and occluded residual reliable extenders in tropacocaine, norcocaine, cis- and trans-cinnamoylcocaine, benzoylecgonine samples; and caffeine, phenacetin, levamisole and hidroxizine. In the quantitative samples analysis lower cocaine purity found is 64.58% and the highest is 95.83%. In relation to the presence of residual compounds, 136 of them are detected. Some are preliminarily identified. This work explores the possibility to use these compounds for the comparison of chromatographic profiles looking forward to establish different links in cocaine samples. The results contribute to the knowledge of forensic chemistry and the toxicology potential of cocaine hydrochloride samples produced and seized in Colombia.